1987
DOI: 10.1083/jcb.105.3.1183
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid sequence of the human fibronectin receptor.

Abstract: Abstract. The amino acid sequence deduced from eDNA of the human placental fibronectin receptor is reported. The receptor is composed of two subunits: an 0t subunit of 1,008 amino acids which is processed into two polypeptides disulfide bonded to one another, and a 13 subunit of 778 amino acids. Each subunit has near its COOH terminus a hydrophobic segment. This and other sequence features suggest a structure for the receptor in which the hydrophobic segments serve as transmembrane domains anchoring each subun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
256
1
3

Year Published

1991
1991
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 555 publications
(269 citation statements)
references
References 53 publications
9
256
1
3
Order By: Relevance
“…The ß, chimera also localized to focal contacts in cells plated in serum, suggesting that it also binds to proteins in focal contacts formed by vitronectin receptors . The 03 and ß, intracellular domains may bind to the same cytoskeletal protein, since the N3 and ß, intracellular domains have considerable homology (Argraves et al ., 1987 ;Fitzgerald et al ., 1987) and colocalize with the same cytoskeletal proteins at adhesion sites (Fath et al ., 1989) . Interestingly, the 03 intracellular domain can substitute for the ß, intracellular domain in het- (Solowska et al, 1991) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ß, chimera also localized to focal contacts in cells plated in serum, suggesting that it also binds to proteins in focal contacts formed by vitronectin receptors . The 03 and ß, intracellular domains may bind to the same cytoskeletal protein, since the N3 and ß, intracellular domains have considerable homology (Argraves et al ., 1987 ;Fitzgerald et al ., 1987) and colocalize with the same cytoskeletal proteins at adhesion sites (Fath et al ., 1989) . Interestingly, the 03 intracellular domain can substitute for the ß, intracellular domain in het- (Solowska et al, 1991) .…”
Section: Discussionmentioning
confidence: 99%
“…2, A-D). Although the integrity of these chimeras was confirmed by nucleotide sequence analysis, we were also able to demonstrate by immunofluorescence that (Leonard et al ., 1984 ;Nikaido et al ., 1984), and either the entire as intracellular domain from Lys 1022 to the translational stop codon (Argraves et al ., 1987) or the entire 0, intracellular domain from Lys 753 to the translational stop codon (Argraves et al ., 1987) . (A and B) or the ß1 (C and D) chimera were plated on coverslips in serum for 36 h and stained for the transfected receptor with polyclonal antibodies to the IL-2 receptor (A and C) and for the endogenous fibronectin receptor with mAb 11 (B and D).…”
Section: Expression Ofthe Chimeric Receptorsmentioning
confidence: 99%
“…Among at least 22 different a/b-heterodimers, the b1-integrin is the most widespread receptor subunit existing in combination, for example, with a5 the fibronectin receptor (Argraves et al, 1987) and with a1, a3 or a6 receptors for laminin or collagen (Hynes, 1992). Initiated integrin clustering after cell -ECM attachment activates intracellular effectors that are capable of coupling integrins and growth factor receptors to specific downstream targets such as b1-integrin-linked kinase (ILK) (Hannigan et al, 1996) or focal adhesion kinase (Schaller and Parsons, 1994).…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] A common characteristic of all integrins is their absolute requirement for divalent cations, such as Mg 21 and Ca 21 , to function. 3,4,[6][7][8][9][10][11] These cations presumably exert their effects by binding to the 3-5 putative cation-binding domains located on all integrin a subunits, 12 and possibly by interacting directly with b subunits. 13 We have recently demonstrated that a 2 b 1 integrin-mediated pancreatic cancer cell adhesion to Type I collagen, an ECM protein shown to be highly upregulated in pancreatic cancer [14][15][16][17] and to promote the malignant phenotype in vitro and in vivo, [18][19][20][21][22][23][24][25] is promoted in 1.5 mM Mg 21 and inhibited in 1.5 mM Ca 21 , 21 and that the a 2 b 1 integrin from pancreatic cancer cell lysates bound specifically to Type I collagen by affinity chromatography in 3 mM Mg 21 , can be eluted with 3 mM Ca.…”
mentioning
confidence: 99%